La facultad sancionadora y su importancia en el sistema tributario en el Ecuador. - Alburqueque Garcia, Cindy Viviana (My University, 2018)
The breach of tax obligations and erroneous behavior by taxpayers, were causes for what was considered the need to grant the Tax Administration Sanctioning Faculty with the function of sanctioning and correcting those infractions preventing illicit tax. The sanctioning power represents for the tax administration a tool to counteract the breach of tax obligations by taxpayers, with the aim of reducing non-compliance with them. The granting of the sanctioning authority to the Tax Administration has made the management of the tax system more efficient, seeing the results of the tax collection that have nowadays become the main source of income for the state budget, because of that has decreased the infractions by the taxpayers. An analysis will be made on the importance of the sanctioning faculty for the management of the Tax Administration in the Ecuadorian tax system. The methodology that has been used in this research is the bibliography, because relevant information is collected through scientific articles, regulations, etc., obtaining data from reliable sources that will be reflected in the criteria of various authors who support the development of the job. It is necessary to make the taxpayers aware of the damages they generate by not acting responsibly before the obligations they have with the tax administration and the possible sanctions to which they would be subject.
El incumpliendo de las obligaciones tributarias y las conductas erróneas por parte de los contribuyentes, fueron causas por lo que se consideró la necesidad de otorgar a la Administración Tributaria la Facultad Sancionadora con la función de sancionar y corregir aquellas infracciones previniendo ilícitos tributarios. La facultad sancionadora representa para la administración tributaria una herramienta para contrarrestar el incumplimiento de las obligaciones tributarias por parte de los contribuyentes, con el objetivo de disminuir el incumplimiento de las mismas. El otorgar la facultad sancionadora a la Administración Tributaria, ha provocado que la gestión del sistema tributario sea más eficiente, al ver los resultados de la recaudación tributaria que han logrado hoy en día ser la principal fuente de ingresos para el presupuesto de estado, a motivo que ha disminuido las infracciones por parte de los contribuyentes. Se realizará un análisis sobre la importancia de la facultad sancionadora para la gestión de la Administración Tributaria en el sistema tributario ecuatoriano. La metodología que se ha utilizado en la presente investigación es la bibliográfica, porque se recopila información relevante a través de artículos científicos, normativas, etc.., consiguiendo datos de fuentes fidedignas que se verán plasmados en los criterios de diversos autores que apoyan el desarrollo del trabajo. Es necesario concientizar a los contribuyentes de los perjuicios que generan al no actuar con responsabilidad antes las obligaciones que tienen con la administración tributaria y las posibles sanciones a las que estarían siendo sujeto.
Keywords: IMPORTANCIA; SANCIONADORA; TRIBUTOS; OBLIGACIONES; INCUMPLIMIENTO